Current Training and Continuing Education Needs of Preschool and School-Based Speech-Language Pathologists Regarding Children With Cleft Lip/Palate - Bedwinek, Anne P.; Kummer, Ann W.; Rice, Gale B.; Grames, Lynn Marty (Language, speech & hearing services in schools, 2010)
Purpose: The purpose of this study was to obtain information regarding the education and experience of preschool and school-based speech-language pathologists (SLPs) regarding the assessment and treatment of children born with cleft lip and/or palate and to determine their continuing education needs in this area. Method: A 16-item mixed-methods survey to collect quantitative and qualitative data was distributed via postal mail to a geographically diverse random sample of 565 preschool and school SLPs. Results: The response rate was 59%. With an average of 15.93 years in practice, respondents reported that they infrequently saw children with cleft lip/palate. When treating these children, respondents wanted communication with the cleft-craniofacial team, accessible continuing education through Web sites and conferences, and clinically practical information relevant to the school setting. Conclusion: When assessing and treating a low-incidence population such as children with cleft-related communication disorders, school-based SLPs need accessible, accurate continuing education resources and collaboration with specialists in the field.